A random small molecule library screen identifies novel antagonists of the kinin receptor from the cattle fever tick, Rhipicephalus microplus (Acari: Ixodidae). Issue 5 (2nd February 2021) - Xiong, Caixing; Baker, Dwight; Pietrantonio, Patricia V
Abstract: BACKGROUND: The southern cattle tick, Rhipicephalus microplus, is a primary vector of the deadly bovine disease babesiosis. Worldwide populations of ticks have developed resistance to acaricides, underscoring the need for novel target discovery for tick control. The arthropod‐specific R. microplus kinin receptor is such a target, previously validated by silencing, which resulted in female reproductive fitness costs, including a reduced percentage of eggs hatching. RESULTS: In order to identify potent small molecules that bind and activate or inhibit the kinin receptor, a high‐throughput screening (HTS) assay was developed using a CHO‐K1 cell line expressing the recombinant tick kinin receptor (BMLK3 ). A total of ~20 000 molecules from a random in‐house small molecule library were screened in a 'dual‐addition' calcium fluorescence assay. This was followed by dose–response validation of the hit molecules identified both from HTS and an in silico screen of ~390 000 molecules. We validated 29 antagonists, 11 of them were full antagonists with IC50 values between 0.67 and 8 μmol L –1 . To explore the structure–activity relationships (SAR) of the small molecules, we tested the activities of seven analogs of the most potent identified antagonist, additionally discovering three full antagonists and four partial antagonists. These three potent antagonists (IC50 < 3.2 μmol L –1 ) were validated in vitro using the recombinant mosquito kinin receptor and showed similar antagonistic activities. In vivo, these three compounds also inhibited the mosquito hindgut contraction rate induced by a myotropic kinin agonist analog 1728. CONCLUSION: Antagonists identified in this study could become pesticide leads and are reagents for probing the kinin signaling system. © 2021 Society of Chemical Industry Abstract : High‐throughput screening and in silico screening of small molecule libraries on the recombinant tick kinin receptor yielded 36 antagonists. The three most potent antagonists also inhibited contractions of the insect hindgut. © 2021 Society of Chemical Industry.